Pertimbangan laboratoris arah pemasangan rotasi gigitiruan sebagian lepasan rangka logam Laboratory considerations in rotational path of insertion of metal frame removable partial denture - FX Ady Soesetijo (DiscoverSys Inc., 2011)
Clinical indications and contraindications for insertion path of removable partial denture (RPD)have been welldiscussed in the literature. However, specific discussion of proper laboratory technique and procedure for dentaltechnician is scarce and limited. This article describes two problems that dental technicians occasionally encounterwhich make the fabrication of rotational insertion path of RPD difficult or impossible. Design modifications by theclinician can eliminate problems faced by technicians in determining the proper path of insertion. Lack of clinicalexperience and/or guidance from the literature related to the insertion path of RPD design may cause laboratoryand clinical problems. The recognition of these potential problems will minimize the laboratory and clinicalproblems